O SOFTWARE SCILAB NA FORMAÇÃO DE PROFESSORES – DO EXERCÍCIO AO CENÁRIO INVESTIGATIVO UM CAMINHO DE PERSPECTIVAS - Avi, Peterson C.; Avi, Emanueli B.; Pereira, Tânia M.; Fahl, Daniel; Sakis, Maria A. (Salão do Conhecimento, 2013)
Resumo